âPETHEKANâ: KONTROL SOSIAL PADA MASYARAKAT TRADISIONAL TENGGER - Hadi, Nur (Jurnal Sejarah dan Budaya, 2010)
Abstract. Social control is one mechanism to prevent social deviation and also is a work of the community so each one obey the rule and values that applied in the community. The obedience is needed to ensure the continuity of community life. The community of Tengger has developed a social control called âPethekanâ. Their working-together habit has tought them how local knowledge developed to ensure the continuity of their life social in a solid and harmonious state.